2006
DOI: 10.4049/jimmunol.177.3.1670
|View full text |Cite
|
Sign up to set email alerts
|

New Generation Vaccine Induces Effective Melanoma-Specific CD8+ T Cells in the Circulation but Not in the Tumor Site

Abstract: Although increasing evidence suggests that CTL are important to fight the development of some cancers, the frequency of detectable tumor-specific T cells is low in cancer patients, and these cells have generally poor functional capacities, compared with virus-specific CD8+ T cells. The generation with a vaccine of potent CTL responses against tumor Ags therefore remains a major challenge. In the present study, ex vivo analyses of Melan-A-specific CD8+ T cells following vaccination with Melan-A peptide and CpG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 44 publications
3
105
0
Order By: Relevance
“…The present data are in agreement with our previous report 17 that vaccination with peptide, CpG and IFA induced higher CD8 T-cell numbers and more pronounced effector differentiation than vaccination with DNA, recombinant viral vectors, or peptides and proteins in vaccine formulations without CpG. 22 Following multiple booster vaccinations, T-cell responses were maintained at high levels over extended periods of time, confirming previous data on cancer-specific human CD8 Tcells. 35,36 The functionality on a per T-cell basis was increased in patients with high T-cell frequencies, as observed previously in mice and humans.…”
Section: Tumor Immunologysupporting
confidence: 82%
See 1 more Smart Citation
“…The present data are in agreement with our previous report 17 that vaccination with peptide, CpG and IFA induced higher CD8 T-cell numbers and more pronounced effector differentiation than vaccination with DNA, recombinant viral vectors, or peptides and proteins in vaccine formulations without CpG. 22 Following multiple booster vaccinations, T-cell responses were maintained at high levels over extended periods of time, confirming previous data on cancer-specific human CD8 Tcells. 35,36 The functionality on a per T-cell basis was increased in patients with high T-cell frequencies, as observed previously in mice and humans.…”
Section: Tumor Immunologysupporting
confidence: 82%
“…3b) which is characteristic for advanced differentiation of virus-specific CD8 T-cells. 22 This is not usually observed after T-cell vaccination, except after vaccination with peptide and CpG. When comparing patients with strong T-cell responses (>0.5% of tumor-specific cells) with those with weaker T-cell responses, we found that the former contained significantly higher proportions of CD28 neg cells (Fig.…”
Section: Specific T-cells Correlate With Functionmentioning
confidence: 80%
“…As a result a potent, cell-mediated T H 1 response is initiated. A humoral immune response is also initiated as TLR9 agonists enhance differentiation of B cells into antibody-secreting plasma cells, potentially promoting antibody-dependent cellular cytotoxicity (Appay et al, 2006). An understanding of the immune cascade initiated by TLR9 activation has prompted the clinical development of several TLR9 agonists in the fields of infectious disease, cancer and asthma/allergy.…”
Section: Toll-like Receptormentioning
confidence: 99%
“…These CpG ODN adjuvants have been heavily studied for the treatment of infectious diseases, and several clinical trials are also investigating their activity as tumor vaccines. The addition of CPG 7909 to a peptide MART-1 vaccine in patients with human leukocyte antigen-A2 þ melanoma caused an approximate 10-fold increase in the number of antigen-specific CD8 þ T cells (Speiser et al, 2005;Appay et al, 2006). Anti-MAGE-3 antibody titers were enhanced with the addition of CPG 7909 to a MAGE-3 recombinant protein vaccine in a phase I/II trial, and one patient had a durable objective response (PR for 9 þ months) (van Ojik et al, 2002).…”
Section: Tlr9 Agonists As Vaccine Adjuvantsmentioning
confidence: 99%
“…As yet no truly successful anti-melanoma vaccine has been developed, although various strategies have been tested. In general, numerous tumour-reactive T lymphocytes can be detected in the patient's blood following vaccination, but tumour growth is unaffected (Arienti et al, 1996;Lee et al, 1998;Baurain et al, 2000;Appay et al, 2006). One explanation is that the tumour microenvironment is so immunosuppressive that any incoming effector cell is impeded (Appay et al, 2006).…”
mentioning
confidence: 99%